A Cost Comparison for Telehealth Utilization in the Kidney Transplant Waitlist Evaluation Process. Issue 2 (February 2018) - Forbes, Rachel C.; Rybacki, Diane B.; Johnson, Tommy B.; Hannah-Gillis, Angela; Shaffer, David; Hale, Douglas A.
Abstract : Background: There have been limited publications on telehealth utilization in transplantation with no prior reports of telehealth-related costs for pretransplant evaluations. The aim of this study is to compare costs throughout the evaluation process for those patients assessed initially by telehealth with those seen in-person. Methods: All patients approved for kidney transplant waitlist evaluation at our center from March 2013 thru May 2016 with decisions were included in this study. Patients approved for evaluation were scheduled for either an initial telehealth or in-person visit, partly based on patient factors. Clinically related and travel-related costs were calculated. Time estimates for patient time needed to complete visit, time from application approval to initial visit, and time from application approval to decision were obtained. Comparisons were made using t tests. Results: Thirty-nine months were included for 302 patients. All categories of clinically or travel-related costs were significantly less for the telehealth cohort ( P < 0.0001). Total mean cost per patient was US 656.11 versus US 1108.91 for the cohort initially evaluated by telehealth versus in-person ( P < 0.001). The time needed to complete an evaluation (1.7 vs 2.4 days, P < 0.001) and the time to initial evaluation (51.4 vs 87.9.0 days, P < 0.001) were significantly less in the telehealth cohort. The cohort seen by telehealth was older with increased comorbidities (<0.001). Conclusions: As telemedicine applications continue to proliferate, we present our experience with telehealth for initial kidney transplant waitlist evaluations with associated reductions in cost and time which may also improve access to transplantation. Abstract : This study shows that costs and time to complete an evaluation for pretransplantation kidney waitlist are significantly lower for those patients assessed initially by telehealth compared to those seen in-person, possibly reducing disparities of distance and travel costs for patients.